Experimental Study on MICP Aqueous Solution under the Action of Different Organic Substrates - Huai-miao Zheng; Ling-ling Wu; Kai-wen Tong; Lin Hu; Qing Yu; Gui-cheng He; Zhi-jun Zhang (Geofluids)
The precipitation rate and cementation strength of calcium carbonate crystals during the process of microorganism-induced calcium carbonate precipitation (MICP) are key factors that affect the application effect of this technology. In order to improve the quality of calcium carbonate formation in the MICP process, egg white protein with a volume fraction of 20%, bovine serum albumin with a mass fraction of 0.3%, sucrose with a mass fraction of 5%, bamboo leaves with a mass concentration of 25 g/L, and bamboo leaf-magnesium chloride (Mg2+/Ca2+=4:1) were added during the experiment of different groups of MICP solutions. The results of the solution test study showed that there was no obvious lag period for bacterial growth under the action of organic matrix. The concentration of bacteria in the reaction solution was higher under the action of sucrose and egg white. The conversion rate of Ca2+ under the action of egg white was the fastest, which was about 2.5 times higher than that of the control group. After 14 days of grouting reaction, it was found that the proportion of calcite-type calcium carbonate produced under the action of egg white was the highest, and the Ca element accounted for 66.24% in the solidified material. Sucrose was second; bovine serum albumin was the lowest. The calcium carbonate crystals generated by the control of each organic matrix had a high degree of pore size matching with the tailings under a dry-wet cycle. The structural characteristics of the calcium carbonate crystals, such as crystal form, morphology, and particle size, were mainly due to the interaction between the organic matrix and the calcium carbonate crystals. This study proves that the addition of the organic matrix can improve the formation rate and crystal structure of calcium carbonate during MICP, thus providing a new reference for the development of MICP technology.